(untitled) (diségno, 2021)
The architectures ‘forgotten’ in the drawer, as Vittorio Magnago Lampugnani stated in his 1982 volume, La realtà dell’immagine. Disegni di architettura nel ventesimo secolo, are those representations which, without being debased by compromises, give back the idea of architecture in its highest vision, ideational and projectual purity (read more).